2023
DOI: 10.3390/biomimetics8060450
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization Induced by Biomimetic Hydroxyapatite Toothpastes on Human Enamel

Alexandra-Diana Florea,
Lucian Cristian Pop,
Horea-Rares-Ciprian Benea
et al.

Abstract: This work aimed to compare the effect of four new toothpastes (P1–P4) based on pure and biomimetic substituted nano-hydroxyapatites (HAPs) on remineralization of human enamel. Artificially demineralized enamel slices were daily treated for ten days with different toothpastes according to the experimental design. Tooth enamel surfaces were investigated using atomic force microscope (AFM) images and surface roughness (Ra) determined before and after treatment. The surface roughness of enamel slices was statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…A number of studies have shown that Coca-Cola ® decreased the salivary pH immediately after consumption [35][36][37]39,40], but generally it did not produce a decrease in salivary pH below 5.5 [35][36][37]. The pH value of 5.5 was found to be critical for enamel dissolution and caries development in vitro [56,61]; at the same time, in vivo this value varies over a wide range depending on the individual characteristics of the enamel and the content of mineral ions in plaque fluid and saliva [73][74][75]. In relation to erosion, critical pH is reversely proportional to the calcium and phosphate concentrations not only in the saliva and plaque fluid, but also in the foods and drinks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of studies have shown that Coca-Cola ® decreased the salivary pH immediately after consumption [35][36][37]39,40], but generally it did not produce a decrease in salivary pH below 5.5 [35][36][37]. The pH value of 5.5 was found to be critical for enamel dissolution and caries development in vitro [56,61]; at the same time, in vivo this value varies over a wide range depending on the individual characteristics of the enamel and the content of mineral ions in plaque fluid and saliva [73][74][75]. In relation to erosion, critical pH is reversely proportional to the calcium and phosphate concentrations not only in the saliva and plaque fluid, but also in the foods and drinks.…”
Section: Discussionmentioning
confidence: 99%
“…BF active ingredients include Zn-hydroxyapatite and a probiotic. Remineralizing properties of hydroxyapatite are well documented [53][54][55][56]94,95]. Biomimetic (hydroxyapatite-containing) oral care products replicate the natural structure of teeth and can promote the remineralization of hard tooth tissues [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…atomic force microscopy (AFM) is also a suitable technique for evidencing changes in enamel topography because it can provide more quantitative results on surface roughness. Several articles have been published that use the AFM technology to track erosion and demineralization changes in enamel [47][48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%